Comparison of seismic response of high-rise RC buildings with Tubular system -tube in tube- considering the effect of soil structure Interaction (Damascus University Journal for engineering sciences, 2023)
Tube-in-tube is considered as one of the most important seismic resistant structural systems in high rise RC buildings, this system usually consists of an outer tube composed of special moment resisting frames (SMRF) and an inner tube that consists of shear walls. The soil structure interaction (SSI) has role in determining the behavior of the structural system, that could be taken in to account or not. depending on the structural system and soil type.This research presents an analytical study using dynamic analysis according to Abaqus 2019 program, to compare the seismic response of several high RC building models that use the tube in tube system and have two different heights, by taking the effect of two kinds of soils, rocky and gravel-silt soils comparing to the fixed base case (without soil effect).The results have showed an increase in storey displacements in the presence of gravel–silt soil compared to structures with fixed base, while the results in rocky soil and fixed base were so close. In addition, taking soil effect led to a decrease in base shear values unless resonance is not close.
Keywords: Soil structure interaction (SSI); tube in tube system; gravel silt soil; rocky soil; dynamic analysis; finite element method